"Plantations in the political economy of colonial sugar production: Natal and Queensland, 1860-1914" - Graves, Adrian; Richardson, Peter (My University, 1979)
Since 1650 the production of cane sugar for sale in international markets for domestic and industrial consumption has been dominated by the plantation as the unit of production. This form of production has been associated with many tropical agricultural crops in the Caribbean, Central America, Brazil and the Southern United States, but has always had a particularly close association with sugar. Such forms of production, which developed within the economic organization of the mercantalist empires of seventeenth century Europe; have traditionally been almost synonymous with the institution of slavery. (1) However, the freeing of slaves in all the plantation districts of the New World between 1834 and 1836 did not brine about an immediate end to this type of agricultural production. Indeed, the rapid growth of the international economy throughout much of the nineteenth century actually encouraged the maintenance of sugar plantations, and did much to facilitate their emergence in other parts of the world. Cuban sugar plantations, for example, did not reach their pre-eminent position in world markets until the use of slave labour had actually been rejected by the planters themselves. (2) Moreover, Natal and Queensland, areas with no traditional association with commercial sugar' production or slavery, developed a form of wage labour plantation for the production of augar after I860, which drew heavily upon the organizational experience of other sugar colonies.
African Studies Seminar series. Paper presented 27 August, 1979